Optimalisasi Sumber Daya Lokal melalui Literasi Ekonomi: Kunci Peningkatan Kesejahteraan di Desa Perkebunan Maryke - Rizka Aldira Marpaung; Maysa Aureli; Jelita Dwi Cahya (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
The optimization of local resources is a key strategy in improving community welfare, particularly in rural in Perkebunan Maryke Village. Through economic literacy, communities can be empowered to understand, manage, and effectively and sustainably utilize the potential resources around them. This article discusses the role of economic literacy in strengthening the community's capacity to manage local resources to achieve better economic welfare. It also explores how empowerment programs, such as the Community Service Program (KKN), can act as catalysts in expanding the community's understanding of economics, particularly in managing local assets such as agriculture, fisheries, and handicrafts. The study results show that good economic literacy enables communities to make more informed decisions regarding investment, production, and marketing of local products, which ultimately contributes to increased income and social welfare. Therefore, strengthening economic literacy is a strategic step in empowering communities to become more economically independent through the utilization of their local resources.